Design, Synthesis, and Antifungal/Anti-Oomycete Activities of Novel 1,2,4-Triazole Derivatives Containing Carboxamide Fragments - Jiali Wang; Haoran Shi; Aidang Lu (Journal of Fungi, 2024)
Plant diseases caused by pathogenic fungi or oomycetes seriously affect crop growth and the quality and yield of products. A series of novel 1,2,4-triazole derivatives containing carboxamide fragments based on amide fragments widely used in fungicides and the commercialized mefentrifluconazole were designed and synthesized. Their antifungal activities were evaluated against seven kinds of phytopathogenic fungi/oomycete. Results showed that most compounds had similar or better antifungal activities compared to mefentrifluconazole’s inhibitory activity against Physalospora piricola, especially compound 6h (92%), which possessed outstanding activity. Compound 6h (EC50 = 13.095 μg/mL) showed a better effect than that of mefentrifluconazole (EC50 = 39.516 μg/mL). Compound 5j (90%) displayed outstanding anti-oomycete activity against Phytophthora capsici, with an EC50 value of 17.362 μg/mL, far superior to that of mefentrifluconazole (EC50 = 75.433 μg/mL). The result of molecular docking showed that compounds 5j and 6h possessed a stronger affinity for 14α-demethylase (CYP51). This study provides a new approach to expanding the fungicidal spectrum of 1,2,4-triazole derivatives.